Novel Ultra-Fast Liquid Chromatography Method for Simultaneous Quantification of Metformin Hydrochloride and Remogliflozin Etabonate - PANCHAL, J; Dhalani, J. (Asian Journal of Chemistry, 2023)
An advanced formulation having remogliflozin etabonate (REM) and metformin hydrochloride (MET) for the treatment of diabetes was recently approved. However, there hasn't been any information reported on a UFLC technique for simultaneously quantifying both active substances. Therefore, aim of the study was the development of an ultra-fast isocratic liquid chromatography method for quantification of MET and REM in API and dosage form. The reversed phase-UFLC method was developed with a very short run time of only 3 min with no interference due to blank. The compounds were separated using Shimadzu Sim-pack XR ODS (75 mm × 3 mm, 2.2 μ) column with mobile phase consisting of buffer (0.1% phosphoric acid):acetonitrile (30:70). The developed method was validated as per ICH-Q2(R1). The linearity was established in the range of 0.01-125 ppm and 0.01-25 ppm for MET and REM, respectively. The average assay was found 99.4% for MET and 99.1% for REM. The accuracy was observed 98.29-99.49% for MET and 98.39-99.73% for REM. The proposed method is very fast and simple however precise and accurate. This method is very useful for regular quality control laboratory to quantify MET and REM in API and dosages forms.